THE LATTICE BOLTZMANN METHOD FOR FLUID MIXING: A COMPARISON WITH THE FINITE ELEMENT METHOD - NADANIELA EGIDI (TASK Quarterly, 2004)
In this article we study three-dimensional mixing of an incompressible viscous fluid subjected to the force of rotating blades in a vessel, with a low Reynolds number. The results obtained with the lattice Boltzmann method are compared with the ones previously obtained using the finite element method. All the qualitative and quantitative parameters of the two simulations agree.